The Effect of Endosulfan in GnRH and GtH Genes Expression of Male Hard-Lipped Barb (Osteochilus vittatus C.V.) - asrul sahri siregar; pudji astuti; yulia sistina; norman arie prayogo (Universitas Jenderal Soedirman, 2020)
The presence of pollutants in water makes the environment toxic to all living biota and affects reproduction in fish. One of such pollutants is endosulfan, which is an off-patent organochlorine insecticide, widely used in various agricultural activities. Endosulfan is extremely toxic to fish and all other aquatic organisms, showing a range of chronic effects, including genotoxicity, and reproductive issues. Therefore, the aim of the research was to find the effect of endosulfan on cGnRH, sGnRH, GtH-I and GtH-II gene expression inmale hard-lipped barb fish. These fish were kept in aquarium containing several levels of endosulfan (0 mg/L [control]; 0.88 mg/L [low level]; 1.76 mg/L [medium level]; and 2.64 mg/L [high] level) for 60 days. The effects of endosulfan on GnRH performance on the fishwere evaluated by the expressions of these genes; cGnRH-II, sGnRH, GtH-I, and GtH-II. In the 8th week, there was a decrease in the expression of all the four genes in fish with high dose of endosulfan compared with the control group (P < 0.05). These findings showedthat endosulfan inhibits the expression of cGnRH, sGnRH, GtH-I and GtH-II genes in male hard-lipped barb.